(3JMaI ef CQGO GdGgJOG aj eYQaI Gdhba hGdGHJOGs - (3MSjf GdLhgQj GdeTghQ HGdSQOjs; (3GdaGSj , YHO Gddg Hf eSYhO GdeZQHj,J (B1147 (3g` s
(3ChdgG (B:s
(3ajbhd GdYHO GdabjQ MSjf GdLhgQj GdeTghQ HGdSQOj Cf SjOi CMeO Hf GdTjN YHOGdcQje GdCTehfj GdeGdcj bO Ufa cJGHkG hSeGg efGQ GdgOi aj HjGf Gdhba hGdEHJOG hGNJUQg s
(3BNQgG (B:s
(3hbhdg GdNfGS def QaY eG HYOg NHQ deHJOC eMPha Ch fUHg Ydi GdPe hdjS Hhba def LQg fYJkG deG bHdg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B150s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs